ホッピョウヨウ ニオケル ソコガタ プランクトンコオリ ホッピョウヨウ ノ イチジセイサン ノ キホン コウゾウ トシテノ カイヒョウ チュウ ノ ビサイ ソウルイ ノ ゾウショクニツイテ - 目黒, 煕; メグロ, ヒロシ; 伊藤, 邦幸; イトウ, クニユキ; 福島, 博; フクシマ, ヒロシ; MEGURO, Hiroshi; ITO, Kuniyuki; FUKUSHIMA, Hiroshi (国立極地研究所, 1967)
P(論文) A summer field survey off Point Barrow, Alaska, revealed a growth of photosynthetic diatoms in Arctic sea ice. The diatoms are found in a brine solution in microfissures between ice crystals on the underside of the ice. The chlorophyl content of this layer is 100 times that of the surrounding sea waters. Arctic sea ice is found to be neither a closed frozen system that disallows transportation of nutrient substances nor a completely inactive biochemical habitat owing to the extremely low tempereture. Glaciologically it is a kind of seasonal nutrient metabolism associated with desalinization of sea ice and photosynthesis by diatoms. A considerable fraction of the primary production of the Arctic Sea may occur in sea ice. departmental bulletin paper